La vitamina E y la inmunidad de las aves - Madrigal-Rojas, Sergio (Universidad de Costa Rica, 2013)
Research done in the last 20 years has shown that vitamin E plays an important role in the development and modulation of the immune system. At least three mechanisms have been described of how the vitamin E modulates the birds immune system. The first mechanism is related with the antioxidant function of vitamin E on the cells of the immune system, maintaining the integrity of these cells and assuring an optimum immune response. The second mechanism is associated with the synthesis of eicosanoids, which modulate the production of prostaglandin and leukotrienes. The last one is associated with the synthesis of interferon and its antiviral response.Experimental evidences have shown that the immune response modulation through the supplementation of vitamin E improves diseases resistance in poultry. It is possible that the levels required to achieve this goal are higher than the level normally used by the industry to optimize productive parameters. Laboratory and field trials have shown that supplementation levels between 150 y 250 mg/kg of vitamin E improves the inmunocompetence of poultry and this can be translated into better productive and economic performance.